2023
DOI: 10.7717/peerj.14855
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum FGF21 levels predict heart failure during hospitalization of STEMI patients after emergency percutaneous coronary intervention

Abstract: Background Fibroblast growth factor 21 (FGF21) has multiple cardioprotective effects including modulation of glucolipid metabolism, anti-inflammation, and anti-oxidative stress, but its association with the heart failure during hospitalization in patients with ST-segment elevation myocardial infarction (STEMI) undergoing emergency percutaneous coronary intervention (PCI) has not been reported. Methods A total of 348 STEMI patients treated with emergency PCI were included from January 2016 to December 2018. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
2
2
0
1
Order By: Relevance
“…Tucker et al 43 reported that FGF‐21 is involved in the pathophysiology of HF by preventing oxidative stress, cardiac hypertrophy, and inflammation in cardiomyocytes and that its level is elevated in patients with HF, suggesting that FGF‐21 may be used as a biomarker for the prediction and diagnosis of HF. Another study found that the serum FGF21 levels were elevated in hospitalized patients with ST‐segment elevation myocardial infarction (STEMI), confirming that elevated serum FGF‐21 level may be a strong predictor of HF during hospitalization in patients with STEMI 44 . Together with our results, these reports suggest that FGF‐21 may serve as a biomarker that plays a pivotal role in CAD‐associated HF.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Tucker et al 43 reported that FGF‐21 is involved in the pathophysiology of HF by preventing oxidative stress, cardiac hypertrophy, and inflammation in cardiomyocytes and that its level is elevated in patients with HF, suggesting that FGF‐21 may be used as a biomarker for the prediction and diagnosis of HF. Another study found that the serum FGF21 levels were elevated in hospitalized patients with ST‐segment elevation myocardial infarction (STEMI), confirming that elevated serum FGF‐21 level may be a strong predictor of HF during hospitalization in patients with STEMI 44 . Together with our results, these reports suggest that FGF‐21 may serve as a biomarker that plays a pivotal role in CAD‐associated HF.…”
Section: Discussionsupporting
confidence: 86%
“…Another study found that the serum FGF21 levels were elevated in hospitalized patients with ST-segment elevation myocardial infarction (STEMI), confirming that elevated serum FGF-21 level may be a strong predictor of HF during hospitalization in patients with STEMI. 44 Together with our results, these reports suggest that FGF-21 may serve as a biomarker that plays a pivotal role in CAD-associated HF.…”
Section: Discussionsupporting
confidence: 86%
“…GDF15 and FGF21 Levels in tissue homogenates were examined to reveal mitochondrial dysfunction. GDF15 and FGF21 are circulating markers for mitochondrial disorders and are widely used in diagnosis of mitochondrial diseases[ 7 - 9 ] and other serious diseases, such as liver failure[ 4 , 10 , 11 ], heart failure[ 12 , 13 ], and sepsis[ 14 , 15 ]. Their expression levels positively correlated with disease severity.…”
Section: Resultsmentioning
confidence: 99%
“…Площадь под кривой для FGF21, позволяющая предсказать развитие СН во время госпитализации у пациентов с ИМпST, составила 0,816 (95% ДИ 0,770-0,863). Таким образом, повышенные концентрации FGF21 в сыворотке крови являются значимым предиктором СН во время госпитализации у пациентов с ИМпST после экстренного чрескожного коронарного вмешательства [39].…”
Section: роль Fgf21 при сн: данные клинических исследованийunclassified